The effectiveness of recognizing the definition of verbal meaning in all its elements - Hamidreza Aali; Abolhasan Ghaffari (حکمت اسرا, 2024)
One of the certainties of the knowledge of Islamic logic and one of the most influential components in understanding rational arguments from the perspective of this knowledge is the effective function of verbal indications in certain arguments. Constructive definition of meaning can be a way to know its complete structure, and to define meaning, paying full attention to its elements will play the most important role in this direction, because the set of elements and elements of meaning are its main structure; But studies show that the majority of famous logicians and researchers in this field paid insufficient attention to this issue; Therefore, it is necessary to examine and criticize their definitions about this issue.  The present article with a critical approach to these definitions, such as not paying attention to any of the elements of signification, not mentioning the statement of status, not distinguishing between the signifier and the signified, not mentioning the statement of attribution and limiting itself to the word science, etc., aims to explain the process and integrity. Arkan has provided implications in the definition. In the end, by providing a new definition by mentioning all the elements, the valuable position of implication in reasoning has been made appropriate.